UPAYA MENINGKATKAN KEMAMPUAN LITERASI MEMBACA DI MI UNGGULAN AL-IKHLASH ASSUNNIYYAH DENGAN MODEL PEMBELAJARAN PHONICS - Komarullah, Hafif; Abbas, Achmad Sirojuddin; Nurlita, Meilana Suci (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This community service activity aims to improve the reading literacy skills of first-grade students at MI Unggulan Al-Ikhlash Assunniyyah through the application of the Phonics learning model. The approach used is Participatory Action Research (PAR), which actively involves 1 teacher and 8 students in the process of identifying problems, planning, action, observation, and reflection.. Initial observations revealed low phonemic awareness and reading skills among students, prompting the implementation of the Phonics learning model across three cycles. Each cycle comprised teacher training, classroom practice mentoring, and learning outcome evaluation. The activity results demonstrated significant improvements in phonemic awareness (recognising letter sounds), blending skills (combining sounds into words), as well as increased student interest and active participation in reading instruction. This success was also supported by the use of enjoyable learning media such as phonetic songs, card games, and simple reading modules. Challenges faced included limited teacher understanding and a lack of learning media. However, this activity had a positive impact on improving students' basic literacy skills. Recommendations from this activity include the need for further teacher training and the systematic integration of the Phonics method into the madrasah curriculum.